Improvements in the numerical prediction of fully-suspended slurry flow in horizontal pipes - Messa, Gianandrea Vittorio; Malavasi, Stefano (Powder technology, 2015)
A new two-fluid model is presented for the simulation of fully-suspended liquid–solid slurry flows in horizontal pipes. The model is a significant upgrade of an earlier one [G.V. Messa, M. Malin, S. Malavasi, Powder Technol. 256 (2014), 61–70], and the main improvements concern the use of: (1) a new wall boundary condition for the solid phase (2) a more general correlation for the viscosity of the mixture, which allows accounting for particle shape; (3) a different solution algorithm, which reduces significantly the already low computational burden. By comparison with experimental data available in the literature regarding sand–water slurries, the model showed wider applicability compared to the earlier one. In particular, the validation was carried out for the following flow conditions: pipe diameter between 50 and 200mm; particle size between 90 and 640μm; mean delivered solid concentration up to 40% by volume; and slurry superficial velocity up to 9m/s. Slurries in which the dispersed phase consists of spherical glass beads have been briefly explored too. The improvements considerably increase the accuracy of the pressure gradient predictions, without affecting the model's capability in reproducing the other features of these flows of most engineering interest, namely solid volume fraction distribution and velocity distribution. [Display omitted] •New two-fluid model for slurry pipeline flows•New wall boundary condition for the solid phase•Innovative modeling of grain properties•Efficient solution algorithm•Wider applicability and higher accuracy compared to an earlier model